G334 'This might be a silly question?' – a new teaching format. (24th May 2017) - Syed, T; Prentice, P; Jones, V
Abstract : Aim: We aimed to develop a new format of teaching session, using questions submitted by the paediatric multidisciplinary team. We invited colleagues at all levels to ask questions, with the rule that no question was 'too silly' to ask. Questions were encouraged covering paediatric practice, particularly questions with no clear answer from the literature, training, and work-life balance. Methods: Questions could be submitted by an identified participant or anonymously, using a submission box on the ward, email or the sli.do website. Voting was encouraged using the sli.do website, to identify the most popular questions and prioritise answering them. We answered questions using a combination of literature search before, and peer discussions during, teaching sessions. Collated 'answers' were then emailed to the whole paediatric team. Questions or discussions which could inform further teaching sessions or change practice were used whenever possible. Results: To date, 5 teaching sessions have been held over an 8 month period. 26 people have contributed a total of 50 questions. 66% of the most popular questions have been answered. The majority of questions relate to clinical practice. Questions varied from 'should we always avoid NSAIDs in chicken pox?' to 'when is the best time in training to have a baby?' Several questions related to management of wheeze, and to training, and informed separate teaching sessions on 'asthma', and 'training routes and how to access support'. A question about the use of PEEP on resuscitaires prompted the purchase of new T-pieces in the department. Discussion: Our main outcome has been the successful development of this teaching style, with extremely positive feedback from participants. Teaching has been specifically tailored to attendees, answering the most popular questions asked. Peer discussion has emphasised that many questions (both medical and non-medical) may not have straightforward 'correct' answers, which is an important learning point in itself. Additionally, this teaching has contributed to quality improvement, with the introduction of PEEP on resuscitaire T-pieces. It has also informed changes to our overall teaching programme, using recurring themes from questions in our 'part-task', simulation and regular 'drug of the month' teaching sessions.